Coconut – the tree of life - Murthy, B N S (Indian Horticulture, 2019)
Coconut is called the Kalpavriksha or tree of abundance. It is an important food crop of economic importance to many Asian and Pacific countries in the world. The crop provides livelihood security and employment opportunities to major segments of the rural mass of these countries. India being the largest coconut producing country in the world, occupies 31% of global production. The coconut palm provides food security and livelihood opportunities to more than 12 million people in India. It is also a fibre-yielding crop for more than 15,000 coir-based industries which provides employment to nearly 6 lakh workers of which 80% are women folk. The crop contributes around ` 2,50,000 million (US$ 3788 M) to the country’s GDP and earns export revenue of around ` 43,654 million (US$ 661 M). Coconut and coconut products are gaining global importance as a contributing factor to the health, nutrition and wellness of human beings. This is due to its multiple medicinal and nutraceutical properties being revealed day by day. This new development in health sector brought in unprecedented increase in demand of coconut products in domestic and international markets. It is estimated that there are 5 million coconut holdings and 12 million farmers in our country covering 17 states and 3 Union Territories, says Dr B N S Murthy, Hort. Commissioner, Government of India.